TO STUDY THE EFFICACY OF PRATISARANIYA KSHARA IN THE MANAGEMENT OF VISARAPA (CELLULITIS) (International Journal of Ayurveda and Pharma Research, 2017)
Acharya Sushruta, father of Indian surgery (Shalya Tantra) was well aware of importance of Visarpa and their management in surgical practices. Clinical features of Visarpa explained by Acharya Sushruta are very much resembles inflammatory swelling like as cellulitis. In Ayurveda cellulitis may be compared to Visarpa, it is a skin and subcutaneous tissue diseases. This skin diseases is of a particular type and its spreads very fast like snake, hence it is called Visarpa.As per modern science cellulitis explained as an infection of the deeper layer of the skin and the underlying tissue. Cellulitis is characterized by an acute, diffuse, spreading, edematous, suppurative inflammation of the dermis and subcutaneous tissues. Alepa â€“poulticing applying paste of drugs etc on the Vranashopa is the first treatment, it is common for all kinds of swelling and very important one also. Poulticing is beneficial in unripe swellings, it mitigates the Dosha and relieves burning sensation, itching and pain. it is foremost in clearing the skin, muscle and blood by removing their blemishes and best to relive burning sensation, pain and itching. So keeping above assumption in mind related with Kshara and Visarapa we have planning the present study to add newer concept of Ayurveda regarding Kshara application in management of Visarpa to existing scientific knowledge. And hence present study entitled â€œTo Study the efficacy of Pratisaraniya Kshara in the management of Visarapa (cellulitis)â€. The present study designed as Prospective randomized control single blind clinical trial and hypothesis will be consider as Pratisaraniya Kshara act as a Shoshana, Shodhana, Lekhana, Ropana and Shothahar properties in management of Visarpa. On the basis of hypothesis study will be designed in 2 groups, Pratisaraniya Kshara will selected for external application in management of Visarpa (cellulitis) in experimental group while Magsulf dressing [Magnesium Sulphate (Mgso4)+Glycerin] in control group, each group will selected 30 patients as per inclusion and exclusion criteria. On the basis of observation, data analysis will be drawn and result will be analyzes after that discussion and conclusion will be drawn accordingly.